Induction of TFF1 gene expression in pancreas overexpressing transforming growth factor α. (1st July 1999) - Ebert, M P A; Hoffmann, J; Haeckel, C; Rutkowski, K; Schmid, R M; Wagner, M; Adler, G; Schulz, H U; Roessner, A; Hoffmann, W; Malfertheiner, P
Abstract : BACKGROUND/AIMS: Chronic pancreatitis is an inflammatory disease of the exocrine pancreas associated with extensive fibrosis, enlarged pancreatic ducts, acinar cell degeneration, and the formation of tubular complexes. The molecular and biochemical alterations associated with these histological changes are not kown. Generally, the new family of TFF peptides (formerly known as P-domain peptides or trefoil factors) is aberrantly expressed during chronic inflammatory diseases of the gastrointestinal tract. METHODS: Using human pancreatic tissues obtained from patients with chronic pancreatitis and murine pancreatic tissues obtained from transgenic mice overexpressing transforming growth factor α (TGF-α), the expression and cellular distribution of TFF1 was analysed using northern blot analysis, polymerase chain reaction (PCR), and immunohistochemistry. RESULTS: In the normal human pancreas, TFF1 was scarce, with only a few ducts exhibiting cytoplasmic TFF1 immunoreactivity. In contrast, human chronic pancreatitis tissue specimens exhibited strong TFF1 immunoreactivity in ductal cells, areas of ductal hyperplasia, and tubular complexes. Semiquantitative PCR analysis of TFF1 mRNA levels showed enhanced expression of TFF1 in the pancreas of patients with chronic pancreatitis. Furthermore, TFF1 mRNA levels were detectable in the pancreas in four of five transgenic mice overexpressing TGF-α. In contrast, four of five wild type mice did not exhibit a TFF1 mRNA transcript. In addition, while no specific TFF1 immunoreactivity was present in the pancreas of the wild type mice, ductal epithelial cells and duct-like tubular complexes in the pancreas of the transgenic mice overexpressing TGF-α exhibited pronounced TFF1 immunoreactivity. CONCLUSIONS: Ductal cells and tubular complexes in pancreatic fibrosis express TFF1. As the 5′-flanking region of TFF1 contains an epidermal growth factor responsive enhancer region and the expression of epidermal growth factor and TGF-α is enhanced in pancreatic fibrosis, the enhanced expression of TFF1 in pancreatic fibrosis may be mediated by TGF-α.